Robot-assisted simple prostatectomy vs endoscopic enucleation of the prostate: a systematic review and meta-analysis of comparative trials - Kowalewski, Karl-Friedrich; Hartung, Friedrich; Hardenberg, Jost von; Haney, Caelán Max; Kriegmair, Maximilian; Nuhn, Philipp; Patroi, Paul; Westhoff, Niklas Christian; Honeck, Patrick; Herrmann, Thomas Reinhard William; Michel, Maurice Stephan; Herrmann, Jonas (Journal of endourology, 2022)
Context: Robot-assisted simple prostatectomy (RASP) and endoscopic enucleation of the prostate (EEP) are two minimally invasive alternatives to simple prostatectomy, which is considered the standard treatment in large prostate glands. It remains unclear which of the two is superior in terms of outcome and complications. Objective: To compare perioperative and functional outcomes of RASP vs EEP. Evidence Acquisition: A systematic review and meta-analysis was conducted according to the recommendations of the Cochrane Collaboration and in line with the PRISMA criteria. The database search included clinicaltrials.gov, Medline (via PubMed), CINAHL, and Web of Science and was using the PICO criteria. All comparative trials were considered. Risk of bias was assessed with the revised ROBINS-I tool. Evidence Synthesis: Seven hundred sixty studies were identified, 4 of which were eligible for qualitative and quantitative analysis, reporting on a total of 901 patients with follow-up up to 24 months. Hemoglobin drop (mean difference [MD] confidence interval [CI]: 0.34 g/dL [0.09-0.58]), the rate of blood transfusions (odds ratio [OR] [CI]: 5.01 [1.60-15.61]) catheterization time (MD [CI]: 3.26 days [1.30-5.23]), and length of hospital stay (LoS) (MD [CI]: 1.94 days [1.11-2.76]) were significantly lower in EEP. No significant differences were seen in operating time and enucleation weight. No significant differences were observed in the incidence of postoperative urinary retention, postoperative transient incontinence, and complications graded according to the Clavien-Dindo classification. Functional results were similar, with no significant differences in International Prostate Symptom Score and maximum urinary flow rate at follow-up. Conclusion: Both EEP and RASP offer excellent improvement of symptoms due to prostatic hyperplasia. EEP has lower blood loss, shorter catheterization time, and LoS and should be the first choice if available. RASP remains an attractive alternative for extremely large glands, in concomitant diseases, or whenever EEP is not available. Review Registration Number (PROSPERO): CRD42021226901
Gesehen am 23.10.2023